Men perspectives on attending antenatal care visits with their pregnant partners in Misungwi district, rural Tanzania: a qualitative study - Maendeleo Boniphace; Dismas Matovelo; Rose Laisser; Hadija Swai; Victoria Yohani; Sylvia Tinka; Lusako Mwaikasu; Hannah Mercader; Jennifer L. Brenner; Jennifer Mitchell (BMC, 2021)
Abstract Background Mens'attendance with their pregnant partners at facility-based antenatal care (ANC) visits is important for maternal and child health and gender equality yet remains uncommon in parts of rural Tanzania. This study examined men's perspectives on attending ANC with their pregnant partners in Misungwi District, Tanzania. Methods Twelve individual interviews and five focus group discussions were conducted using semi-structured questionnaires with fathers, expectant fathers, and in-depth interviews were done to health providers, volunteer community health workers, and village leaders. Interviews were recorded and transcribed in Swahili and later translated to English. The research team conducted thematic analysis to identify common themes among interviews. Results We identified two broad themes on the barriers to male attendance at facility-based ANC visits: (1) Perceived exclusion during ANC visits among men (2) Traditional gender norms resulting to low attendance among men. Conclusion Attendance at health facility for ANC visits by men with their pregnant partners in the study areas were challenged by structural and local cultural norms. At the facility men were uncomfortable to sit with women due to lack of specific waiting area for men and that they perceived to be neglected. Local cultural norms demanded women to have secrecy in pregnancy while men perceived not to have a role of being with their partners during ANC visits.